2005
DOI: 10.1016/j.limno.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic fungi growing on dead fragments of submerged plants

Abstract: The authors investigated the dead fragments of 22 species of submerged plants in the water from three limnological and trophical different water bodies (spring, river and pond). A total of 184 species of aquatic fungi, including 119 zoosporic and 65 conidial species were found on the fragments investigated plants. The most common fungus species were Aphanomyces laevis, Saprolegnia litoralis, Pythium rostratum (zoosporic fungi) and Acrodictys elaeidicola, Anguillospora longissima, Angulospora aquatica, Lemonnie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
(27 reference statements)
0
21
1
Order By: Relevance
“…These studies demonstrated that plants such as corn, rice, sorghum, onions, soybeans, tomatoes, cotton, carrots, lettuce, sunflowers, and duckweed are not affected by prolonged exposure to high dosages of several developmental stages of L. giganteum (21). This oomycete remains primarily a host-specific pathogen of mosquito larvae that is not typically associated with plants, although, like many other aquatic fungi and oomycetes (24), it can also grow saprophytically on rotten vegetation (25).…”
mentioning
confidence: 99%
“…These studies demonstrated that plants such as corn, rice, sorghum, onions, soybeans, tomatoes, cotton, carrots, lettuce, sunflowers, and duckweed are not affected by prolonged exposure to high dosages of several developmental stages of L. giganteum (21). This oomycete remains primarily a host-specific pathogen of mosquito larvae that is not typically associated with plants, although, like many other aquatic fungi and oomycetes (24), it can also grow saprophytically on rotten vegetation (25).…”
mentioning
confidence: 99%
“…Czeczuga et al 2005). In recent years, molecular methods such as clone libraries, fingerprint analysis, and phylogenetic trees have increasingly been used in aquatic mycology to include the 'unculturable' and sterile (i.e.…”
Section: Methodology For Characterizing Fungi Within Their Ecosystemmentioning
confidence: 99%
“…Similar to the LMDM, the use of micromanipulators permits studying interspecies relationships independent of experimental setups and may help connecting species to their natural substrate preferences. Conventional studies, based on microscopical examination and identification (Czeczuga et al 2005, van Ryckegem et al 2007) can be used to update sequence databases and to complete original descriptions with molecular definitions.…”
Section: Further Methods Of Great Potentialmentioning
confidence: 99%
See 2 more Smart Citations